Effect of physical environment and community behavior on dengue hemorrhagic fever (DHF): A literature review - Anliyanita, Roza; Anwar, Chairil; Fajar, Nur Alam (Universitas Islam Negeri Alauddin Makassar, 2023)
Dengue Hemorrhagic Fever (DHF) or Dengue Hemorrhagic Fever (DHF) is caused by the dengue virus which is transmitted by Aedes aegypti and Aedes albopictus mosquitoes. The spread of this disease has become a significant global health problem, especially in countries with high levels of poverty. The purpose of this study is to understand the role of factors such as geography and social norms in the spread of dengue disease, so that it becomes the main motivation in investigating the spread of dengue cases. The approach used in this study is a Systematic Literature Review. The sources used include various international and national journals accessed through platforms such as PubMed, Google Scholar, and Scopus between 2019 and 2023. There were 22 selected articles that met the exclusion and inclusion criteria. The results of this study involve the impact of the physical environment and human behavior on DHF. Dengue prevention efforts include actions such as emptying water containers, closing water storage containers, increasing used goods, using abate powder, keeping clothes dry properly, installing wire nets in vulnerable areas, using mosquito repellent lotions, and maintaining cleanliness and behavior. good in general. Therefore, it is hoped that the village head will initiate a DHF prevention program by involving the community in cleaning the physical environment through mutual cooperation activities and the local health center will implement the DHF prevention program.